"We are not like those who/…/sit in the woods and drink": The making of drinking spaces by youth. (May 2020) - Ander, Birgitta; Wilińska, Monika
This article applies the concepts of place and space to understand youth and their engagement in risky behavior, such as drunkenness. It is based on the prolonged engagement with 23 underage youth coming from smaller municipalities in the south of Sweden. The study was comprised of semi-structured interviews, field visits, and observations at sites relevant for youths. In the stories narrated by youth, drunkenness is no longer an ad hoc activity conducted somewhere at the margins of society. The construction of drinking spaces was accomplished through highly managed, monitored, and organized practices, such as sending out invitations in advance, planning how much alcohol to drink, designating drivers, and securing transport means. Crucial to this was that spaces were products of relations existing between various youth, with no adults present. Spaces of drinking changed as those who participated in their construction changed. In addition, certain rules and codes of conduct (e.g. taking care of friends who drunk too much) were enforced to assure that the constructed spaces provided a sense of safety and enabled having fun. We conclude this article by arguing that a focus on place and space brings forward vital aspects in understanding the role of transforming party spaces that would otherwise remain obscure to social work knowledge and practice.